Analysing secondary vortex structures in an hp turbine stage using the realisable k-Ω SST model - Yershov, S.V.; Swirydczuk, J. (Інстиут проблем машинобудування ім. А.М. Підгорного НАН України, 2010)
The article analyses the effect of turbulence model selection on the pattern of development and interaction of secondary vortex structures in an HP turbine stage. The basic tool used in the analysis is FlowER, a specialised code developed for studying flow through fluid-flow machine stages and stage sections. The flow calculations performed using a standard k-ω SST turbulence model presented highly unstable behaviour of the rotor passage vortex, which periodically built up, moved up along rotor blade suction side and broke down. On the other hand, the use of the modified version, taking into account realisability constraints, has made it possible to stabilise the rotor passage vortex behaviour. Проанализировано влияние выбора модели турбулентности на характер развития и взаимодействия вторичных вихревых структур в турбинной ступени высокого давления. Основным инструментом, используемым при анализе, был решатель FlowER – специализированный код, предназначенный для исследования течений в изолированных ступенях и группах ступеней турбомашин. Расчет течения, выполненный с использованием стандартной модели турбулентности k-ω SST, показал существенно нестационарный характер канального вихря в решетке ротора, который периодически появлялся, перемещался вдоль стороны разрежения лопатки ротора в радиальном направлении и разрушался. Применение модифицированной версии решателя, учитывающей ограничения реализуемости, позволило стабилизировать поведение этого вихря.